1983
DOI: 10.1515/jnet.1983.8.3.183
|View full text |Cite
|
Sign up to set email alerts
|

Transport Studies with Aqueous Solutions of Urea and Thiourea Across an Ionexchange Membrane

Abstract: Experimental results for the measurement of hydrodynamic permeability, electro-osmotic velocity, electro-osmostic pressure and streaming potential for different aqueous solutions of urea and thiourea across the cation-exchange membrane (Indion 236, Sd fine chemicals, India) at 30 °C and voltages up to 25 V are reported. The results have been analysed in the light of thermodynamics of irreversible processes. The cation-exchange membrane has been characterised in terms of effective cross-sectional area, equivale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…s and equation (4) general it can be seen that the maximum efficiency is extremely low because the cross-phenomenological coefficient L 21 , which represents the electricalmechanical coupling, is also very small (-ºÏ" 11 m 3 /Vs), [7]. Similar results have been found with both weakly charged and ion-exchange membranes [1][2][3][4][5][6]. This implies that a large part of the input energy is dissipated in the electrokinetic processes.…”
Section: Influence Of the Plug Characteristicssupporting
confidence: 71%
See 3 more Smart Citations
“…s and equation (4) general it can be seen that the maximum efficiency is extremely low because the cross-phenomenological coefficient L 21 , which represents the electricalmechanical coupling, is also very small (-ºÏ" 11 m 3 /Vs), [7]. Similar results have been found with both weakly charged and ion-exchange membranes [1][2][3][4][5][6]. This implies that a large part of the input energy is dissipated in the electrokinetic processes.…”
Section: Influence Of the Plug Characteristicssupporting
confidence: 71%
“…Thus, for plugs with different structural characteristics (5) may be written as: (6) where D is a constant which includes the parameters characterizing the liquid permeant: (7) …”
Section: Influence Of the Plug Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…occurring across the ionic membranes which have been described by Spiegler [20]. Blokhra et al [21][22][23][24][25][26] have also reported the transport phenomenon of various electrolytes and non-electrolytes across different types of diaphragm using the thermodynamics of irreversible processes. It is expected that the electrical double layer in highly charged membranes would be more sensitive to the change in characteristics depending on the nature of the permeants which would naturally be reflected in transport properties, For better understanding and prediction of a membrane's permeation characteristics, an insight into the structural details, e.g.…”
Section: Introductionmentioning
confidence: 97%